Pengaruh Penggunaan E-Modul Asam Basa berbasis Guided Discovery Learning terhadap Kemampuan Literasi Membaca dan Numerasi Peserta Didik - Salsabila, Diva; Yerimadesi, Yerimadesi; Gazali, Fauzana; Aini, Faizah Qurrata (Universitas Negeri Padang, 2025)
The Acid Base E-Module based on Guided Discovery Learning (GDL) has been validated and tested for practicality, but its effectiveness and impact on students' reading and numeracy literacy have not yet been tested. The purpose of this study is to analyze the effect of using e-modules on improving reading and numeracy literacy among Phase F students at SMAN 3 Bukittinggi. This research is a quasi-experimental study using a non-equivalent control group design. The research population included Phase F students at SMAN 3 Bukittinggi, with samples from classes XI F 3 and XI F 4 selected using purposive sampling. This study uses test instruments to evaluate students' reading literacy and numeracy skills. Data analysis employs N-gain tests, normality tests, homogeneity tests, and hypothesis tests. The study results show that the average N-gain for reading literacy in the experimental class (0.52) is higher than that of the control class (0.5). The normality and homogeneity tests showed a normal and homogeneous distribution in reading literacy. The hypothesis test using the t-test produced a tcount value (2.0032) that was greater than the ttable value (1.9955). The average N-gain in the experimental class for numeracy literacy (0.36) was also higher than that of the control class (0.26). Normality and homogeneity tests produced a normal and non-homogeneous distribution in numeracy literacy, and the t’ test produced a t’count value (3.5492) greater than the ttable value (2.0058). These findings indicate that the application of the acid-base e-module with the GDL approach has a significant impact on reading and numeracy literacy.